2005
DOI: 10.1038/nri1668
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of immune responses by L-arginine metabolism

Abstract: L-Arginine is an essential amino acid for birds and young mammals, and it is a conditionally essential amino acid for adult mammals, as it is important in situations in which requirements exceed production, such as pregnancy. Recent findings indicate that increased metabolism of L-arginine by myeloid cells can result in the impairment of lymphocyte responses to antigen during immune responses and tumour growth. Two enzymes that compete for L-arginine as a substrate - arginase and nitric-oxide synthase - are cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
1,430
4
19

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,541 publications
(1,485 citation statements)
references
References 140 publications
32
1,430
4
19
Order By: Relevance
“…Inhibiting arginase degradation of arginine may lead to decreased downstream products such as polyamines and proline [30]. These products are important mediators of cellular proliferation and collagen synthesis, respectively [31]. Thus, there may be potential adverse effects on liver regeneration and wound healing in animals treated with an arginase inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting arginase degradation of arginine may lead to decreased downstream products such as polyamines and proline [30]. These products are important mediators of cellular proliferation and collagen synthesis, respectively [31]. Thus, there may be potential adverse effects on liver regeneration and wound healing in animals treated with an arginase inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…The activation by the classical pathway results in the production of NO, synthesized from arginine by inducible NO synthase (iNOS) [13,17]. The alternative metabolic pathway for arginine is catalysed by arginase, which converts arginine to ornithine and urea [13].…”
Section: Introductionmentioning
confidence: 99%
“…The activation by the classical pathway results in the production of NO, synthesized from arginine by inducible NO synthase (iNOS) [13,17]. The alternative metabolic pathway for arginine is catalysed by arginase, which converts arginine to ornithine and urea [13]. It has been shown that macrophages from Th1 strains of mice (C57BL ⁄ 6, B10D2) preferentially use the iNOS pathway and macrophages from Th2 strains of mice (BALB ⁄ c, DBA ⁄ 2) preferentially use the arginase pathway [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 In the B6SJLF1 model, where myeloid cell expansion is more protracted, an extrinsic regulatory role of these cells on the observed in vitro T-cell proliferative responses cannot be excluded. The expansion of myeloid progenitor cells in these chimeras is reminiscent of the myeloid-derived suppressor cells described in association with myelosuppression, GvHD, tumors and chronic infections 21,29 where they have been implicated in tumor-specific and nonspecific T-cell dysfunction. [30][31][32] Our earlier data, 21 and more recently those of others, 33 suggest that these cells may have a role in controlling GvH reactivity.…”
Section: Discussionmentioning
confidence: 99%